216. Biological treatment planning with multiple ion beams. (December 2018) - Sokol, O.; Scifoni, E.; Hild, S.; Durante, M.; Krämer, M.
Abstract : Purpose: To exploit the potential and different advantages of different ion beams when used at the same time, in a mixed irradiation, accounting for biological effects (relative biological effectiveness (RBE) and oxygen enhancement ratio (OER)) at an advanced level in inverse planning. Methods: Firstly, a biologically oriented treatment planning system for particles (TRiP98) was upgraded with the possibility to perform "kill painting"[1] in hypoxic targets, i.e. restoring a uniform cell killing in the all over the target, accounting for the differently oxygenated regions. The code is further enabled to perform simultaneous biological optimization of multiple ion species (MIBO), especially tuned for cases of hypoxic tumors. Calculation on idealized geometries as well as on selected patient cases have been considered. Results: A comparative assessment of treatment plans using different ion beams singly or in combinations has been performed. In particular, the use of oxygen beams appears to be more effective when used in combination with lower LET ions like He, rather than using only oxygen beams[2] ; improvements up to a 12% relative effect can be found, on the level of peak to entrance ratio for idealized geometries, as well as in critical organs sparing in test patient plans cases. Conclusions: MIBO can provide in selected conditions an indication for an alternative treatment, where combination of different ions lead to better therapeutic ratio as compared to any of the single ion plans. The present approach has been proposed and accepted to be tested on in vitro phantoms at the MIT ion beam facility (Marburg, Germany) which provides different ions in a fast source switching mode.